Ultrastructure of the digestive tract in neotropical carnivorous catfish Hemisorubim platyrhynchos (Valenciennes, 1840) (Siluriformes, Pimelodidae) - Faccioli, Claudemir Kuhn [UNESP]; Chedid, Renata Alari [UNESP]; Mori, Ricardo Hideo [UNESP]; Amaral, Antônio Carlos do [UNESP]; Vicentini, Irene Bastos Franceschini [UNESP]; Vicentini, Carlos Alberto [UNESP] (Wiley-Blackwell, 2015)
The surface of the digestive tract of Hemisorubim platyrhynchos was analyzed by scanning electron microscopy. Morphometric studies by transmission electron microscopy were performed to analysis the intestinal microvilli. H. platyrhynchos is a Neotropical carnivorous freshwater catfish featuring a short digestive tract composed of a short esophagus, saccular stomach, and intestine with four regions: anterior, middle, posterior, and rectal. The esophageal surface is constituted by fingerprint-like microridges that anchor the mucosubstances secreted by goblet cells facilitating the passage of food. Goblet cells present the opening to the esophageal lumen, between the microridges. Club cells are in basal epithelium and they do not present the opening to the lumen. The gastric luminal surface shows polygon-shaped epithelial cells which secrete granules by exocytose to protect the gastric surface. The intestinal luminal surface reveals folds that are thicker in the anterior intestine than in the posterior intestine, increasing the absorptive surface area. The intestinal surface presents the microvilli of enterocytes and the opening of goblet cells. The morphometric analysis showed that the microvilli are longer in the anterior intestine, significantly decreasing towards the posterior intestine. The microvilli surface area significantly is greater in the anterior and middle intestine than in the posterior intestine. Numerous openings of goblet cells were observed in the posterior intestine acting in epithelial protection and lubrication. SCANNING 9999:1-8, 2015. © 2015 Wiley Periodicals, Inc.
Keywords: Hemisorubim platyrhynchos; Microvilli; Morphometry; Surface analysis